What is the role of HER2-specific antibody immunity in patients with HER2-positive early breast cancer receiving chemotherapy plus trastuzumab? - Mehanna, Joe; Haddad, Fady GH.; Eid, Roland; Lambertini, Matteo; Kourié, Hampig Raphaël (Translational Cancer Research, 2018)
Breast cancer is the most common malignancy among women worldwide and the leading cause of cancer death in many countries (1). In around 20% to 25% of breast cancer cases, there is an overexpression of HER2 or an amplification of its gene (HER2-positive subtype); HER2 is a transmembrane receptor implicated in tumor replication, invasion and dissemination (2). HER2-positive breast cancer is characterized by a worse prognosis, aggressive disease, higher mitotic index, worse nuclear grade and lymph nodes positivity (3).